(untitled) (Experimental biology, 2016)
In the article, the authors to assess and current a complete geobotanical characterization and floristic analysis Ferula iliensis communities in conditions of on the left bank of the Ili river. We have been dentified the population of 91 species of vascular plants belonging to 72 genus, 24 families. Community floristic composition of the population is classified as follows. Belonging to 1 species of gymnosperms, 90 species of angiosperms, although only 13 species from monocots, 77 species from dicots with common family including Chenopodiaceae Vent. (18 species) and Asteraceae Dumort. (18 species) of these major families contains 36 species or 39,6 % species of this association belong to the upper two families. Out of the total 91 plant species identified, 38 species (41.7%) were therophytes (grasses). Of the total species, 5 (5.5%) species are endemic. According to the economic value of the Ferula iliensis communities we have identified 14 groups of useful plants. They note that here the population of this rare, endemic and valuable medicinal plants is not in danger.